Active Learning Environments in Nursing Education: The Experience of the University of Wisconsin‐Madison School of Nursing. (March 2014) - Fahlberg, Beth; Rice, Elizabeth; Muehrer, Rebecca; Brey, Danielle
Abstract : This chapter describes the processes and pedagogies used by one school in transitioning from lecture halls to collaborative learning environments